Political Dimension of Swahili in East Africa: Country and Regional Aspects - M. V. Nikolskaya (Сравнительная политика, 2024)
Kiswahili is an East African Bantu language with around 150 million speakers, including those for whom it is a mother tongue or a language of confident proficiency. Its historical geographic domain spans Tanzania, Kenya and Uganda. All three were part of British East Africa from the early 1920s up until decolonization. At present, their shared history, culture, geographical proximity and integration aspirations make them the core countries in the region. It would be logical therefore to assume that the position of Kiswahili should be growing stronger, yet in reality its status, functions and spread differ across all the three countries. This article seeks to identify the reasons for this phenomenon and analyze whether Kiswahili has the right potential to become a tool for regional political communication and integration.